Religious Moderation and the Struggle for Identity Through New Media: Study of the Indonesian Ahmadiyya Congregation - Siti Solikhati; Adeni Adeni; Farida Rachmawati; Giska Maulidza; Sulaiman Sulaiman (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
This study aims to examine the religious moderation promoted by Ahmadiyah through the website. The Ahmadiyah religious moderation discourse is related to the struggle for identity in the public sphere. This study is qualitative with documentation data collection techniques, namely digging documents containing religious moderation texts found on the Ahmadiyah website. The data are analyzed using a new media approach, which is an approach that sees a text that appears on a new media website as connected to the traditional text of the Holy Book. However, because website media texts relate to the offline world, external factors from social complexity also affect website text building. The results of the study indicate that internally the religious moderation text constructed by Ahmadiyah online comes from its ideology which is indeed fighting for peace and non-violence jihad. Meanwhile, externally, complex social realities in the midst of mainstream authorities and the state also contribute to the moderation text of the Ahmadiyya religion. The values of moderation promoted by Ahmadiyah are, first, supporting the strengthening of nationality by developing the concept of a spiritual and moral caliphate, not a political and militaristic caliphate. Second, strengthening peace and non-violence by encouraging jihad with a pen (jihad bi al-qalam) in response to various emerging social issues. Third, strengthening religious tolerance and freedom by emphasizing openness, not coercion in religion. Fourth, strengthening the existence of local culture by optimizing universal Islamic teachings. In the context of the Ahmadiyya as a minority, the discourse on religious moderation can be said to be an effort to struggle for Ahmadiyya identity in the public sphere in the midst of the mainstream and state authorities. However, this identity struggle seems to be hampered by the problem of Mirza Ghulam Ahmad's (MGA) prophetic position. Therefore, a more massive dialogue is needed with the local Muslim mainstream.